Exploring the association between bioelectrical impedance parameters and body composition in women with and without dysmenorrhea and postmenopause - Suraiya Khatun; Akiko Uchizawa; Emi Kondo; Analiza M. Silva; Yuki Shimamura; Shogo Yamasaki; Yuki Ahagon; Daisuke Hoshi; Yoshiaki Tanaka; Naoki Mukai; Koichi Watanabe; Naomi Omi; et al. (Physiological Reports)
Abstract Female reproductive status influences body composition, including fat mass (FM), fat‐free mass (FFM), and bone health. We aimed to examine differences in body composition, bone health, and bioelectrical impedance analysis (BIA) parameters, including phase angle (PhA), among women with healthy menstruation, dysmenorrhea, and postmenopause. Forty‐five female participants were included and divided into control (healthy menstruation; n = 13), dysmenorrhea (n = 14), and postmenopausal (n = 18) groups. Body composition, bone mineral density (BMD), bone mineral content (BMC), and BIA parameters were measured using dual‐energy X‐ray absorptiometry and multifrequency BIA. The postmenopausal group had significantly lower BMD, BMC, and PhA. In the control group, PhA was positively correlated with body mass, body mass index, FM, FM index, FFM, and FFM index, whereas no correlations were observed in the other groups. Classic bioelectrical impedance vector analysis (BIVA) parameters were consistent with FFM and FFM index, while specific BIVA aligned with body fat. Graphical BIVA analysis showed signs of edema and decreased body cell mass in the postmenopausal group. These findings highlight important differences in body composition, bone health, and bioelectrical parameters across reproductive stages, with a focus on managing muscle loss and edema according to reproductive status.